Ambient temperature correlates with geographic variation in body size of least horseshoe bats. Issue 5 (15th February 2020) - Wang, Man; Chen, Kelly; Guo, Dongge; Luo, Bo; Wang, Weiwei; Gao, Huimin; Liu, Ying; Feng, Jiang
Abstract: Geographic variation in body size is common within many animal species. The causes of this pattern, however, remain largely unexplored in most vertebrate groups. Bats are widely distributed globally owing to their ability of powered flight. Most bat species encounter a variety of climatic conditions across their distribution range, making them an ideal taxon for the study of ecogeographic patterns in body size. Here, we used adult least horseshoe bats, Rhinolophus pusillus, to test whether geographic variation in body size was determined by heat conservation, heat dissipation, climatic seasonality, or primary productivity. We measured body mass and head-body length for 246 adult bats from 12 allopatric colonies in China. We quantified the ecological conditions inhabited by each colony, including mean maximum temperature of the warmest month, mean minimum temperature of the coldest month, temperature seasonality, precipitation seasonality, and annual net primary productivity (ANPP). Body mass and head-body length, 2 of the most reliable indicators of body size, exhibited marked differences between colonies. After controlling for spatial autocorrelation, the mean minimum temperature of the coldest month explained most of the variation in body size among colonies, regardless of sex. The mean maximum temperature, climatic seasonality, and ANPP had limited power in predicting body size of males or females in comparison with mean minimum temperature. These results support the heat conservation hypothesis and suggest adaptive responses of body size to cold climates in cave-dwelling bats.